Anti-Angiogenic Effect of Orally Available Pemetrexed for Metronomic Chemotherapy - Ruby Maharjan; Rudra Pangeni; Saurav Kumar Jha; Jeong Uk Choi; Kwan-Young Chang; Young Kweon Choi; Jin Woo Park; Youngro Byun (MDPI AG, 2019)
Metronomic chemotherapy (MCT) is defined as the frequent administration of low-dose chemotherapeutics, without long drug-free periods, with the exertion of antitumor activity exclusively through anti-angiogenic mechanisms. In this study, we have developed an orally available formulation of pemetrexed (PMX) for MCT. PMX was first complexed ionically with Nα-deoxycholyl-l-lysyl-methylester (DCK) as the permeation enhancer. This was followed by dispersion with poloxamer 188 and Labrasol to form the solid oral formulation of PMX (PMX/DCK-OP). PMX/DCK-OP exhibited a 10.6-fold increase in permeability across a Caco-2 cell monolayer compared to PMX alone. This resulted in a 70-fold increase in the oral bioavailability of PMX/DCK-OP in mice over oral PMX alone. In the A549 xenograft model, tumor volume was reduced by 51.1% in the PMX/DCK-OP treated group compared to only 32.8% in the maximum tolerated dose (MTD)-treated group. Furthermore, PMX/DCK-OP exhibited a significant anti-angiogenic effect on the A549 xenograft mice when compared to the MTD-treated group, as indicated by microvessel density quantification for CD-31. In addition, PMX/DCK-OP enhanced the release of an endogenous angiogenesis inhibitor, thrombospondin-1 (TSP-1), into both the blood circulation and the tumor microenvironment. Therefore, due to its oral route of administration, PMX/DCK-OP appears to be a better alternative to the conventional treatment of PMX.